Algebraic Decomposition Method for Zero Watermarking Technique in YCbCr Space - Nada Mohammed; Areej Abduldaim (Engineering and Technology Journal, 2022)
The close connection between mathematics, especially linear algebra, and computer science has greatly impacted the development of several fields, and the most important is image processing. Algebraic methods aroused interest in building digital image watermarking techniques and are used to find the features of the image to hide the watermark. This paper aims to use the algebraic Hessemberge decomposition method (HDM) for the first time as a transformation to extract the features of the image without using any popular transformation for building zero watermarking. To achieve the aim, two techniques are used, HDM with and without discrete cosine transform (DCT); both depend on the advantage of the algebraic HDM to convert the image to another domain in the YCbCr space. After applying eleven common attacks to images in both techniques, the results showed that the NC values ​​under the influence of many attacks were higher in the second technique than the NC values ​​in the first technique. In contrast, the NC values ​​for salt and pepper attack in the first technique are higher than the NC values ​​in the second technique.